(Enantio)selective Hydrogen Autotransfer: Ruthenium‐Catalyzed Synthesis of Oxazolidin‐2‐ones from Urea and Diols. Issue 27 (13th April 2016) - Peña‐López, Miguel; Neumann, Helfried; Beller, Matthias
Abstract: A novel strategy for the synthesis of oxazolidin‐2‐ones from vicinal diols and urea is described. In this heterocycle synthesis, two different C−O and C−N bonds are sequentially formed in a domino process consisting of nucleophilic substitution and alcohol amination. The use of readily available starting materials and the good atom economy render this process environmentally benign. While this transformation is already highly chemo‐ and regioselective, we also developed the first asymmetric version of this method using ( R )‐(+)‐MeO‐BIPHEP as the chiral ligand. Abstract : Oxazolidin‐2‐ones were synthesized from vicinal diols and urea or carbamates in a ruthenium‐catalyzed process. The sequential formation of one C−O and one C−N bond takes place in a highly chemo‐ and regioselective, atom‐efficient domino process, which can be rendered enantioselective when an appropriate chiral ligand is used.